Consumer Surplus as the Appropriate Standard for Antitrust Enforcement - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
In antitrust enforcement as in cost-benefit analysis, neoclassical economics may be interpreted as arguing for the use of a "total welfare" standard whose implementation treats transfers as welfare-neutral. Several recent papers call for antitrust agencies to move in the direction of this version of a total welfare standard for enforcement. However, as Williamson (1968) noted, horizontal mergers typically result in transfers that may greatly exceed in magnitude any deadweight loss or efficiency gain, so that a decision to ignore transfers may be quite important. I argue that such transfers are likely overall to be quite regressive, and thus that a consumer surplus standard rather than a total welfare standard may be appropriate for antitrust. Two common arguments against this standard – that most mergers are in markets for intermediate goods, and that a consumer welfare standard implies a tolerance for monopsony – are examined and found wanting. I argue in addition that, even if a total welfare standard is used, both the finance literature on merger outcomes and the structure of the U.S. enforcement agencies suggest that the use of a consumer surplus standard by the agencies is more likely to achieve that goal.
Keywords: D02; D31; G34; K21; L40; 330